Improvement of the Pain of Temporomandibular Disorder in Parts of the Human Body through Temporomandibular Joint Correction Treatment - Park, Bo-Ra; Gim, Jeong-An; Baek, Kyung-Wan (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Background and Aim Patients with temporomandibular disorder often experience pain in various parts of the body. However, the degree of improvement of patients’ pain through temporomandibular joint correction has not been identified in an independent study. This study aimed to identify the symptoms most frequently reported by patients with temporomandibular disorder and determine the degree of pain improvement and structural changes through temporomandibular joint correction.Methodology Patients who complained of temporomandibular disorder and visited a dental clinic and agreed to participate were included in the study (n=85). The patients were divided into a nontreatment group (Control, n=35) and treatment group (Treatment, n=50) of the temporomandibular joint, and the treatment group received more than 10 correction treatments. All reported locations of pain were recorded preintervention and postintervention of temporomandibular joint correction treatment, and the degree of pain, which measured using a visual analog scale, was also recorded. Simultaneously, X-ray imaging was performed to confirm the structural difference between the pre-temporomandibular joint and post-temporomandibular joint correction treatment.Result Most of the patients with temporomandibular disorder complained of temporomandibular joint pain (n=66/85), but the majority complained of neck pain (n=61/85) and shoulder pain (n=60/85). In addition, there were many cases of headache (n=26/85), back pain (n=25/85), and lockjaw (n=22/85). In rare cases, complaints of facial pain (n=2/85), tinnitus (n=2/85), hip joint pain (n=4/85), knee pain (n=5/85), xeroma (n=1/85), and ear pain (n=1/85) have been reported. After temporomandibular joint correction treatment, the treatment group had significantly lower visual analog scale scores than pretreatment for TMJ pain, headache, shoulder pain, neck pain, back pain, and lockjaw (p<.0001). Furthermore, it was confirmed that the balance of the cranial bone and mandibular condyle symmetry in the X-ray image was significantly improved in the TMJ correction treatment group (pretreatment vs. posttreatment, p<.001). In the control group, no significant differences were observed pre-and post-intervention in all symptoms and X-ray images.Conclusion Temporomandibular disorders can cause pain in other parts of the body with an unknown cause. Therefore, these results show that if the pain in other parts of the body cannot be fundamentally resolved, temporomandibular joint correction treatment through the diagnosis of temporomandibular disorder may need to be performed in dental clinics.
Keywords: temporomandibular joint; temporomandibular disorder; neck pain; back pain; shoulder pain